Installation of Religious Character Values Through The Usual Prayer of Dhuha Together at SDN Pakamban Daya Pragaan District Sumenep Regency - Fathorrahman - Fathorrahman; Lailatul - Atiqoh (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2023)
Character education is the process of providing guidance to students to become fully human beings with character in the dimensions of heart, mind, body, and feeling and intention. Character education is one of the strongholds and is considered the best solution to need and improve the nation's morals and character which is currently being carried away by the very fast flow of globalization. In Islam, character education has been implemented from an early age, one of which is Duha prayer. The inculcation of religious character values through the habit of praying dhuha is a character education to overcome moral and character degradation in the mindset and behavior of students. This study aims to: (1) describe what character values are instilled through the habit of praying dhuha together at SDN Pakamban Daya. (2) describe the process of cultivating religious character values through the habit of praying dhuha together at SDN Pakamban Daya. This study uses a qualitative descriptive research method. Data collection techniques include 3 ways using observation, interview, and documentation techniques. In this study using data reduction, data presentation and drawing conclusions. The results of this study indicate that: 1). there are 5 characters that exist in students are religious, disciplined, independent, honest and leadership. 2) Duha prayer activities have been carried out for approximately two years and are still ongoing today. The Duha prayer starts at 06.30 – 07.15 WIB every day except Sunday because it is a holiday.Keywords: Istallation of character values, Duha prayer together